Dysfunctional metacognition processes as risk factors for drunkorexia during adolescence. Issue 3 (2nd April 2020) - Laghi, Fiorenzo; Pompili, Sara; Bianchi, Dora; Lonigro, Antonia; Baiocco, Roberto
Abstract: Although metacognitive dysfunction has been associated with eating disorders, to our knowledge no study has yet explored the relation between metacognition and drunkorexia. The aim of the present study was to investigate the potential role of metacognitive processes in drunkorexia in a sample of adolescents. A total sample of 719 adolescents (353 females, 366 boys; age range 15-20) completed a self-report survey composed of Compensatory Eating and Behaviors in Response to Alcohol Consumption Scale, AUDIT-C, Metacognitions Questionnaire-30, and Positive Alcohol Metacognitions Scale. Our results showed that drunkorexia was associated with dysfunctional metacognitive processes; specifically, findings from logistic regression analysis revealed that the metacognitive beliefs in the need to control thoughts, the negative beliefs about the uncontrollability and danger of worrying and the positive metacognitions about alcohol use were significant predictors of drunkorexia. Our study suggests the relevance for prevention efforts to train adolescents to develop alternative self-regulation strategies and more adaptive ways of monitoring thoughts.